Pengaruh Social Media Marketing, Brand Image Dan Brand Equity Terhadap Keputusan Pembelian Chatime (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Angkatan 2020) - Wahyudi, Rochman; Priyono, Achmad Agus; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Universitas Islam Malang Abstract This research aims to analyze and describe the influence of Social Media Marketing, Brand Image, and Brand Equity on the Purchase Decision of Chatime (A Case Study on the 2020 Class of Economics and Business Faculty Students). The population in this study consists of FEB UNISMA students who have made a purchase at Chatime. The sample size was determined using the Malhotra formula, resulting in 95 respondents. Data collection was carried out using a questionnaire. To address the research problems, SPSS software was utilized with various analytical methods, including validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, F-tests, t-tests, and the coefficient of determination (R2) test. The research results indicate that Social Media Marketing does not significantly influence purchase decisions, Brand Image has a significant influence on purchase decisions, and Brand Equity also has a significant influence on purchase decisions. Keywords: Social Media Marketing, Brand Image, Brand Equity, Purchase Decision.